Maximum Likelihood Estimation Approach using the CB-SEM Method: Case Study of Service Quality - Putri Meyla Oktavia; Eri Setiawan; Nusyirwan Nusyirwan; Netti Herawati (Universitas Muhammadiyah Metro, 2023)
The purpose of this study to analyze the service level, satisfaction and loyalty of Sariringgung Beach visitors.Covarian based approach to estimatemaximum likelihood method in the service levelto the satisfaction and loyalty of visitorstourism area of Sariringgung Beach is used. The results of this study indicate that the direct effect of service level to satisfaction is 77%, service level to loyalty is 75%. Whereas the indirect effect of service level on loyalty through satisfaction is 38,5%. Then the total effect of service level on customer loyalty through satisfaction is 73,5%.